Primary Health Care in Preliminary Hypertension Management: A Literature Review - Irvan, Muhammad; Mahfud, Miftakhul Ulum; Mangkuluhur, Adhysta; Faqihudin, Fadli Rizal; Auliansyah, Jundan; Asyari, Rahima Galan (Universitas Muhammadiyah Surakarta, 2024)
Abstract Purpose: The purpose of the article is to evaluate and emphasize the role of primary health care (PHC) in managing hypertension. It systematically reviews the integration of various pharmacological, non-pharmacological, and technological strategies used in PHC to improve hypertension outcomes. By analyzing studies from different regions and methodologies, the article identifies effective interventions, challenges, and areas requiring improvement in hypertension management. Methodology: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard statement. Our search strategy used electronic databases, namely Pubmed, Scopus, and Google Schoolar. Journal searches were conducted in November 2024. Pubmed and Scopus searches used the search keywords